2021
DOI: 10.1111/tri.13989
|View full text |Cite
|
Sign up to set email alerts
|

Cancer transmissions and non‐transmissions from solid organ transplantation in an Australian cohort of deceased and living organ donors

Abstract: Summary Evidence on cancer transmission from organ transplantation is poor. We sought to identify cases of cancer transmission or non‐transmission from transplantation in an Australian cohort of donors and recipients. We included NSW solid organ deceased donors 2000–2012 and living donors 2004–2012 in a retrospective cohort using linked data from the NSW Biovigilance Register (SAFEBOD). Central Cancer Registry (CCR) data 1972–2013 provided a minimum one‐year post‐transplant follow‐up. We identified cancers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…A landmark international study reported a much higher brain tumor transmission risk of 23%, although an unreliable denominator is likely to have inflated this estimate . Our results are consistent with those of recent studies, which found transmission risks of less than 3% . A major limitation of the existing evidence is data quality.…”
Section: Discussionsupporting
confidence: 78%
“…A landmark international study reported a much higher brain tumor transmission risk of 23%, although an unreliable denominator is likely to have inflated this estimate . Our results are consistent with those of recent studies, which found transmission risks of less than 3% . A major limitation of the existing evidence is data quality.…”
Section: Discussionsupporting
confidence: 78%
“…15 SAFEBOD has previously been used to identify missed donation opportunities relating to blood borne viruses 16 and to identify transplants resulting in cancer transmission and nontransmission. 17 …”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13] Mandatory registries, where both numerator and denominator are known, reveal that the frequency of DTC ranges from 0 to 6 cases per 10 000 transplants, and that DTC is usually unknown in the donor before transplantation. [14][15][16][17][18][19][20][21][22][23][24][25][26] One of these studies described the Spanish experience during 1990-2006, reporting a rate of 6 DTCs per 10 000 solid organ transplants. 19 Since then, important changes have occurred in the profile of deceased organ donors in the country, who are becoming older.…”
Section: Introductionmentioning
confidence: 99%